MARKETING OF NUT-BEARING PRODUCTS: CURRENT STATUS AND DEVELOPMENT PROSPECTS (Revista Inclusiones, 2020)
Nut production is one of the most profitable areas of agribusiness. In this study the current state of the Russian market of nut-bearing products has been assessed in the context of the dynamics of foreign economic relations and peculiarities of the global agro-industrial complex. The structure of various nuts import, peculiarities of forming prices and demand for nut-bearing products have been analyzed.